La adicción a la televisión y su incidencia en el comportamiento agresivo de las niñas y niños de preparatoria primer grado de la escuela de educación básica “20 de junio” de la ciudad de Lago Agrio, parroquia Nueva Loja, provincia de Sucumbíos. Período 2014-2015”. Lineamientos alternativos - Requelme Calero, Susana Jacqueline (2015)
This thesis refers to “LA ADICCIÓN A LA TELEVISIÓN Y SU INCIDENCIA EN EL COMPORTAMIENTO AGRESIVO DE LAS NIÑAS Y NIÑOS DE PREPARATORIA PRIMER GRADO DE LA ESCUELA DE EDUCACIÓN BÁSICA “20 DE JUNIO” DE LA CIUDAD DE LAGO AGRIO, PARROQUIA NUEVA LOJA, PROVINCIA DE SUCUMBÍOS. PERÍODO 2014-2015”. LINEAMIENTOS ALTERNATIVOS, made according to the provisions of the Academic Board Regulation of Universidad Nacional de Loja. We raised as General Objective: To raise awareness among parents and children about aggressive behavior because of TV addiction, of children of First grade of school. The methods used for the preparation of this research work were: Scientific, inductive-deductive, analytic-synthetic and Statistical Model, the same that help to achieve the proposed goal. The techniques and instruments used were: a survey which was applied to the parents to identify the television programs watch the children of first grade, of The Basic Education School "20 De Junio" of Lago Agrio city, Nueva Loja parish, Sucumbios province; and an Observation Form applied to children of First Grade, of the Basic Education School "20 De Junio" of Lago Agrio city, Nueva Loja parish, Sucumbios province, to determine aggressive behavior. It is concluded that: 69% of parents surveyed indicated that the types of television programs observe by the son / daughter at home are soap operas, 57% violent cartoons, 51% sports programs, 36% children's programs 20% fight and wars movies; and 8% cultural programs. 76% of parents surveyed indicated that after watching violent television programs, the son imitates screaming, 52% fights, 33% vocabulary; and 17% destruction. With the implementation of the observation form to children, to determine the aggressive behavior, the results indicate that: 57% of children observed never have physical aggressive behaviors, 34% sometimes and 9% always; 62% have never verbal aggressive behaviours, 29% sometimes and 9%; 62% always present gestural, aggressive behavior, 27% sometimes and 11% never.